Технология решения задачи моделирования и прогнозирования на основе индуктивного подхода - Савченко, Е.А. (Кибернетика и вычислительная техника, 2015)
Разработана и описана технология решения задачи моделирования и прогнозирования на основе индуктивного подхода. В ее основе лежит комбинаторный алгоритм МГУА и метод доопределения. Технология позволяет автоматически, по выборке экспериментальных данных, находить модель объекта или процесса с использованием двух внешних критериев выбора: точности и несмещенности. Применение технологии в реальных задачах моделирования и прогнозирования подтвердило ее эффективность. Розроблено та описано технологію розв’язання задачі моделювання та прогнозування на основі індуктивного підходу. В її основі лежить комбінаторний алгоритм МГУА та метод довизначення. Технологія дозволяє автоматично, за вибіркою експериментальних даних, знаходити модель об'єкту або процесу з використанням двох зовнішніх критеріїв вибору: точності і незміщеності. Застосування технології в реальних задачах моделювання та прогнозування підтвердило її ефективність. The purpose of this article is to develop the technology for modeling and forecasting on the experimental data sample based on the combinatorial algorithm. A technology for solving the problem of modeling and forecasting on the basis of the inductive approach was developed and described. This approach is based on the combinatorial algorithm GMDH method and completions. This technology, based on a sample of experimental data, automatically finds the object model or process using two external selection criteria: accuracy and bias. The developed computer technology was tested in solving applied problems of modeling and prediction: in problems of diabetes in a home-based monitoring and problems of modeling the interaction of ions with the surface of the jet gas materials.